In the public sphere: Intimate partner violence against African American single mothers in child paternity disputes - Kalunta-Crumpton, Anita (International review of victimology, 2024)
In the United States, there are high levels of father absence, female-headed single-parent households, and intimate partner violence (IPV) in the African American community. While the relationship between single motherhood and father absence is yet to be showcased in studies of IPV against African American women, its relevance has been evident in the public sphere through the Maury Show (hereon Maury), a US daytime television talk show on paternity disputes. The paper draws on a sample of episodes of Maury and uses content analysis to showcase paternity disputes as a salient context within which African American single mothers can experience nonphysical IPV (i.e. psychological/emotional and economic). In the paternity disputes shown on Maury, patriarchal ideologies and stereotypes of African American women are reproduced to subject African American single mothers to psychological/emotional and economic abuse. Based on the findings, the paper is a call on stakeholders in IPV to prioritize the education of women, particularly single mothers, on the various sites (private and public), contexts and dynamics of nonphysical IPV.